SMEs and Sustainable Entrepreneurship in South Africa: Impact Analysis of Contextual Factors in the Services Sector: Array - Ogujiuba, Kanayo; Nico, R.; Nasiru, M.; Ogujiuba, C.; Estelle, Boshoof (EuroEconomica, 2020)
Objectives: This article establishes the influence of contextual factors on sustainable entrepreneurship in the services sector for SMEs in South Africa. Additionally, it identifies the correlation between the contextual factors and sustainable entrepreneurship. Prior Work: The dynamics of sustainable entrepreneurship is not much known or not in existence amongst SMEs in South Africa. Previous studies have ignored the dynamics of high levels of unemployment, and underemployment, particularly, as it affects SMEs sustainability. Approach: The trustworthiness test of the study instrument was done, using test re-test reliability method, which yielded an R-value of 0.70 and internal consistency of 0.875 as measured by the Cronbach Alpha index. The Binary Logistic technique and Spearman Rank Correlation were used in the analysis. Results: Results indicate that the characteristics of an SME, Government Support, Management Skill, Good employee-employer relationship, and Start-up Capital are correlated to sustainable entrepreneurship. However, the logistic regression only showed three of the factors as having a significant impact on the increase or otherwise of sustainable entrepreneurship amongst the SMEs. Implications: It has become imperative for an overhaul of interventions designed to enhance the SME sector as an important vehicle for addressing the challenges of job creation, economic growth, and equity. Study findings suggest that entrepreneurs and business partners must maintain a posture that continuously pursues novel ideas as per the features of an SME; maintain an opportunity-seeking perspective with employees; and control risks associated with high-risk ventures that bring financial achievements. Value: Sustainable entrepreneurship (SE) is becoming increasingly important for society, and supporting of SMEs is one area where sustainability is critical. The South African Government and other developing countries needs to commit themselves to creating an environment that bolsters sustainability for entrepreneurship to thrive.